Multimode-interference based optical fiber sensor for civil structures monitoring / Chew Sue Ping - Chew , Sue Ping (2020)
The thesis describes the experimental investigations on the multimode interferencebased fiber sensors using single mode multimode single mode (SMS) and multimode single mode multimode (MSM) structures as a sensing device for structural health monitoring (SHM) applications. Both sensor structures were fabricated, characterized and tested for detecting strain and vibration in civil infrastructures. The proposed SMS structure comprises of a short segment of multimode fiber (MMF), which were fusionspliced by two single mode fibers (SMFs) at both terminals. On the other hand, MSM was fabricated by splicing SMF with MMF at both ends. A new packaging technique for the SMS structure was successfully developed to use as water level gauge. The SMS structure was also used to measure the strain in a reinforced concrete beam. The results indicated that the SMS fiber sensor provides sensitivity of 3.7781 nm/(mm/mm) and linearity of 0.96606 in compressive strain measurements to a maximum of 0.116 mm/mm. It was also found that the packaged SMS has much better temperature stability up to 0.0904 nm/°C as compared to unpackaged SMS. On the other hand, the developed MSM based sensor was successfully used to demonstrate a vibration frequency measurement of the mechanical vibration. The structure was capable of detecting wide range of vibration frequency, ranging from 20 Hz up to 6 kHz with high accuracy.